2003
DOI: 10.1177/002215540305100702
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Histochemical Assay for Superoxide Dismutase in Rat Brain

Abstract: S U M M A R Y Superoxide anions are highly reactive radicals overproduced in many pathological situations such as inflammation and ischemia. One of the major factors in the protection from superoxide anions is the enzyme superoxide dismutase (SOD), which catalyzes the dismutation of superoxide to hydrogen peroxide. This study presents a quantitative histochemical method to estimate SOD activity in rat brain tissue sections. This method is based on the cerium capture method and 3,3 Ј -diaminobenzidine amplifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 33 publications
3
9
0
Order By: Relevance
“…We have shown that in the postnatal brain the majority of Cu/Zn SOD immunoreactivity is observed in neuronal somas with less intense staining present in the nuclei, sparing the nucleoli, as has been reported earlier for adult animals [12-17,47]. Accordingly, even though changes in Cu/Zn SOD levels occur in postnatal development, the cell type distribution of this enzyme does not change.…”
Section: Discussionsupporting
confidence: 84%
“…We have shown that in the postnatal brain the majority of Cu/Zn SOD immunoreactivity is observed in neuronal somas with less intense staining present in the nuclei, sparing the nucleoli, as has been reported earlier for adult animals [12-17,47]. Accordingly, even though changes in Cu/Zn SOD levels occur in postnatal development, the cell type distribution of this enzyme does not change.…”
Section: Discussionsupporting
confidence: 84%
“…Also, the defense against reactive oxygen species, which is known to be defective in keratoconus, [19][20][21] is even less efficient in the central part of the cornea. Irradiation of riboflavin with UV light is well known to generate large amounts of superoxide radicals, 22,23 and extracellular superoxide dismutase (SOD-3), a major corneal scavenger of superoxide 20 exists in lower amounts in the central cornea, in particular in the anterior stroma. 20 This and other biochemical differences may contribute to augmented oxidative stress at the corneal center during CXL treatment, with more posttreatment effects on the stroma and augmented light scattering.…”
Section: Discussionmentioning
confidence: 99%
“…There are three isoforms of SOD: mitochondrial manganese SOD (MnSOD), cytosolic copper-zinc SOD (CuZnSOD), and extracellular SOD [49]. Both MnSOD and CuZnSOD have been shown to be induced by different pathological conditions, such as diabetes [50], cerebral ischemia [51], or quinolinic acid-induced lesion [52].…”
Section: Discussionmentioning
confidence: 99%